Memory and Creativity: Finding a Place Where a Heart May Swirl - Cuculiza Brunke, Annemarie (2018)
This article draws from the fieldwork of my MA thesis, “For a Seed to be Born”: Exploring the Links between Emotions and Everyday Creativity in Elementary Teachers´ Classrooms in Peru (Cuculiza, 2017). Informed by collage inquiry (Butler-Kisber, 2008) and memory work (Strong-Wilson, 2015), the fieldwork comprised an arts-based workshop in which participants were asked to explore and reflect on the lived experiences that contributed towards the development of their creativity (Averill, 1999; Runco 2010; Richards 2010). In focusing on the data collected from one of the participants, namely Heart Swirl (pseudonym), I attempt to answer the following questions: In what ways do memory and creativity interconnect? What sorts of spaces are conducive to the investigation of memories in the educational field? In what ways can artistic expression assist memory and creativity? In support of a reflective practice, this article highlights the importance of recognizing how spaces—and the emotions we attach to our memories of these spaces—may be “latent” in our present (Van Manen, 2016). Engaging in play through collage inquiry in an emotionally safe workshop can assist educators in the development of their own creativity and in their ability to become conscious of the ways in which their past lived experiences influence their pedagogy.